(untitled) (Global Journal of Human-Social Science, 2023)
This thesis explores the cultivation of emotional quality in the teaching of choral music in non- professional music colleges in China With the increasing popularity of choral music in China it is important to understand the effectiveness of teaching methods and how students connect emotionally with the genre The research examines the current state of choral music education including the strengths and weaknesses inherent in pedagogical approaches